Transitioning From Open to Robotic Liver Resection. Results of 46 Consecutive Procedures Including a Majority of Major Hepatectomies. (June 2021) - Valverde, Alain; Abdallah, Solafah; Danoussou, Divya; Goasguen, Nicolas; Jouvin, Ingrid; Oberlin, Olivier; Lupinacci, Renato M.
Aims . Minimally invasive liver resection is a complex and challenging operation. Although authors have reported robotic liver resection shows improved safety and efficacy compared with open liver resection, robotic major liver resections for malignant liver lesions treatment remain inadequately evaluated. The aims of the present study were to evaluate the feasibility and safety of transitioning from open to robotic liver resection in a nonuniversity hospital. Patients and Methods. From December 2015 to March 2020, 46 patients underwent totally robotic-assisted liver resections out of 446 robotic procedures. Also, we retrospectively reviewed the last 27 open right hepatectomies (ORHs) and compared then with the first 25 anatomic robotic-assisted right hepatectomies (RRHs). Results . Mean operative time, mean blood lost, rate of complications, and mean hospital stay were associated with the complexity of the procedure. The comparison between ORH and RRH showed that intraoperative complications were less frequently observed during ORH whereas RRH showed a trend in favor of less blood loss. ORH had a trend toward smaller surgical margins and higher rate of R1 resections. Recurrence occurred in 31 (59%) patients and was more frequently observed after ORH. However, the mean follow-up was significantly shorter after RRH. Conclusion . Our study demonstrated the technical feasibility and safety of transitioning from open to robotic liver resection (including major hepatectomies) in a nonuniversity setting. Higher costs remain an important drawback for robotic surgery.